Tinjauan terhadap Alternatif Sistem Pengolahan Senyawa Aktif Farmasi pada Limbah Cair Medis - Fauzan Razansyah; Mindriany Syafila (Jurnal Teknik Lingkungan, 2022)
Hospital wastewater contains various substances that are used for medical, laboratory, research purposes, feces from patients, and also including pharmaceutically active compounds (PhACs). Environmental problems can arise due to the presence of PhAC in water bodies. The active pharmaceutical compounds themselves were originally designed to affect humans and animals physiologically even at low concentrations. These compounds remain in the environment for a long time and are not degraded biologically or naturally. Therefore, to design an WWTP system in hospitals that is able to treat medical liquid waste, research on PhACs is very much needed. This study aims to identify the pollutants contained in hospital wastewater effluent and to review the WWTP system that is able to process hospital wastewater effluent efficiently. Data on non-domestic liquid waste treatment processes were obtained based on research conducted by researchers, so this research was conducted based on literature studies. Indonesia does not yet have regulations governing PhACs in liquid waste, so hospitals in Indonesia have not been able to treat liquid waste that is free of PhACs. Variants of PhACs found in hospital wastewater are very diverse, and this makes it quite difficult to determine an efficient method to degrade PhACs levels in water. However, ozone-based AOPs have been widely used in the field of air remediation because of their low maintenance time, low cost, and high degradation efficiency.